Validation of patient health questionnaire-9 for assessing depression of adults in Bangladesh (Dhaka University Journal of Biological Sciences, 2021)
Depression is one of the most widely recognized and frequently underdiagnosed and undertreated mental health issues around the world. The Patient Health Questionnaire-9 (PHQ-9) has been suggested as the best accessible screening and case-discovering instrument to measure the severity of depression. The investigation aimed to set the reliability and validity of the PHQ-9 for the adults in Bangladesh. A total of 321 Bangladeshi adults (170 males and 151 females) were the study participants. A standard process of three phases was followed to adapt PHQ-9 in Bangladesh. The first phase was forward translation, second phase was Focus Group Discussion and panel of expert's rating and third phase was back translation into original language, piloting and final field data collection. The results showed good reliability of the translated version; the total scale Cronbach’s alpha is 0.837, gender-wise 0.839 for males and 0.841 is for females; similarly, the Spearman-Brown Coefficient is 0.855, and the Guttman Split-half coefficient is 0.848, which indicate the high Split-half reliability as well. The content and construct validity suggest that the Bangla PHQ-9 is a valid tool to assess the depression of Bangladeshi adults. Therefore, the Bangla version of PHQ-9 gives an impression of being a reliable and valid instrument to assess and diagnose depression among Bangladeshi people.Dhaka Univ. J. Biol. Sci. 30(2): 275-281, 2021 (July)